Policy to Accentuate Social Resilience: Disaster Risk Management - Morán, Roberto Carlos Dávila (2022)
The reduction of social vulnerability to disaster risk as a process of political management is presented with high criticality in all areas of application, therefore, the article seeks to determine-through heuristic documentation-guidelines related to management of risks in the face of natural and anthropogenic disasters, which allow minimizing the impact and effects on the social and economic spheres, while building resilience in the communities. Sometimes, the political and technological capacities of governance do not assume risk management from a preventive perspective, rather reactive, therefore, from this research a perspective is proposed from four cosmogonic dimensions: risk identification, management and monitoring, mitigation actions and response capabilities in the event of an event. Finally, it is considered that the good practices of public management complemented with the capacities of the business sector promote social resilience to disasters.